Correlation Between Headroom’s Leadership Style and Implementing Nurse Job Satisfaction In Long Stay Wards of Mangusada Regional Hospital - I Dewa Agung Gde Fanji Pradiptha; Ni Putu Eva Yuliastini Dewi; Nyoman Putri Sriadi; IGAA Sherlyna Prihandhani; Ika Purwanto (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The purpose of this study was to determine the correlation between headroom’s leadership style and implementing nurse job satisfaction in long stay wards of Mangusada Regional Hospital. The design used in this study was Cross-Sectional with 138 sample selected through Purposive Sampling technique. The research instrument used was questionnaire sheet to assess headroom’s leadership style and nurse job satisfaction. The results showed that the headroom used more democratic leadership style (87%) and the level of nurse job satisfaction was more in the moderate category (77.5%). The Lambda statistical test showed that there was correlation between headroom’s leadership style and implementing nurse job satisfaction in the long stay wards of Mangusada Regional Hospital (p-value = 0.008). This research can be used as a reference source for nursing services to increase job satisfaction through a good leadership style